2021
DOI: 10.3390/ijerph18158139
|View full text |Cite
|
Sign up to set email alerts
|

Improving Millennial Employees’ OCB: A Multilevel Mediated and Moderated Model of Ethical Leadership

Abstract: In the field of organizational behavior, the influence of leadership in organizations and the organizational citizenship behavior (OCB) of employees have always been two hot topics studied by scholars. However, previous studies have mainly examined the OCB of baby boomers and Generation Xers. With millennials now entering the workforce, they will highly likely not take the initiative to engage in OCB due to their different values. Scholars have found that millennials respond well to ethical leadership. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 79 publications
(131 reference statements)
0
8
0
Order By: Relevance
“…Finally, in terms of empirical evidence, followers' moral identity (not necessarily virtues-based) mediates the effects of leader humanity-based behaviors (Ete et al, 2020) and ethical leadership (Gerpott et al, 2019) on follower OCBs. Also, Su and Hahn (2021) found that moral identity (though not necessarily virtues-based) moderated the link between ethical leadership and affective well-being, and the indirect influence of ethical leadership on organizational citizenship. Taken together, we anticipate that follower VCMI also mediates the positive relationship between virtuous leadership and follower OCB.…”
Section: Effect Of Virtuescentered Moral Identitymentioning
confidence: 92%
See 4 more Smart Citations
“…Finally, in terms of empirical evidence, followers' moral identity (not necessarily virtues-based) mediates the effects of leader humanity-based behaviors (Ete et al, 2020) and ethical leadership (Gerpott et al, 2019) on follower OCBs. Also, Su and Hahn (2021) found that moral identity (though not necessarily virtues-based) moderated the link between ethical leadership and affective well-being, and the indirect influence of ethical leadership on organizational citizenship. Taken together, we anticipate that follower VCMI also mediates the positive relationship between virtuous leadership and follower OCB.…”
Section: Effect Of Virtuescentered Moral Identitymentioning
confidence: 92%
“…Notably, the direct effect was significant (b 5 0.61, SE 5 0.12, 95% CI [0.38,0.84]). Given the lack of support for H4, a supplemental analysis concerning the possible moderating impact of followers' moral identity (see Su and Hahn, 2021) was conducted. This additional analysis was prompted by Wang et al (2021), who integrated self-concept and social learning theory to argue that the extent to which followers emulate the behaviors of an ethical leader depends on both their moral identity and their identification with the leader.…”
Section: Hypothesis Testingmentioning
confidence: 99%
See 3 more Smart Citations